"AND" logic gate regulated pH and reduction dual-responsive prodrug nanoparticles for efficient intracellular anticancer drug delivery. Issue 1 (10th November 2014) - Bai, Lan; Wang, Xiao-hui; Song, Fei; Wang, Xiu-li; Wang, Yu-zhong
Abstract : A copper ion-based core-cross-linking strategy is used to develop an AND logic gate regulated pH-/reduction-responsive antitumor drug delivery system. Abstract : A dual-responsive drug delivery system simulating an AND logic gate is developed by core-cross-linking of a disulfide-containing anticancer prodrug with Cu 2+ for safe and efficient delivery of anticancer drugs. These prodrug nanoparticles are stable and exhibit nearly no premature drug release, and allow a fast drug release under simulated intracellular conditions, realizing a precise drug delivery towards cell nuclei.